Interactive effect of potassium and cadmium on growth, root morphology and chlorophyll a fluorescence in tomato plant - Rachida Naciri (Nature Portfolio, 2021)
Abstract A hydroponic experiment was conducted to evaluate the role of potassium (K) in tomato plant growth exposed to cadmium (Cd) stress. In this work, the effects of three potassium nutrition regimes (155, 232 and 310 ppm of K) combined with Cd at different levels (0, 12 and 25 µM of CdCl2) on chlorophyll content index, root and shoot dry weights, root morphology, chlorophyll a fluorescence and translocation factor were analyzed. The results showed a negative effect of cadmium, at different concentrations, on all these parameters. However, optimization of K nutrition has shown promising results by limiting the negative effect of Cd. A positive effect of the high concentration of K (310 ppm) was observed on leaf chlorophyll content and chlorophyll a fluorescence compared to 232 and 155 ppm under Cd stress. K supply improved the electron transport at PSI side indicated by the increase in the amplitude of the I–P phase of OJIP transient. Also, K at a concentration of 310 ppm significantly reduced Cd translocation from root to shoot and improved root and shoot growth parameters in the presence of Cd. K supplementation can reduce the negative effect of Cd by improving photosynthesis and promoting chlorophyll synthesis. The optimization of nutrients composition and concentration might be a good strategy to reduce the impact of Cd on plant growth and physiology.